African leaders: Their education abroad and FDI flows - Amelie F. Constant; Bienvenue N. Tien (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Leaders are critical to a country's success. They can influence domestic policy via specific measures that they enforce, and they can also influence international public opinion towards their country. Foreign Direct Investments are also essential for a country's economic growth. Our hypothesis is that foreign-educated leaders attract more FDI to their country. Our rationale is that education obtained abroad encompasses a whole slew of factors that can make a difference in FDI flows when this foreign-educated individual becomes a leader. We test this hypothesis empirically with a unique dataset that we constructed from several sources, including the Library of Congress and the World Bank. Our analysis of 40 African countries employs the robust technique of conditional quantile regression. Our results reveal that foreign education is a significant determinant of FDI inflows, beyond other standard characteristics. While intuitive, this result does not necessarily indicate sheepskin effects or superior human capital obtained abroad. Rather, it indicates the powerful role of the social capital, networks, and connections that these leaders built while they were abroad that they in turn mobilize and utilize when they become leaders.
Keywords: C31; C33; F21; I21; 330; FDI; Leaders' Educational level; return migration; Africa